Harmful alcohol use in rural Uganda: a pilot study from the Kigezi sub-region - Nazarius Mbona Tumwesigye; Vincent Mubangizi; Wilber Karugahe; Agnes Napyo; Sam Maling; Aggrey Mukose; Catherine Gitige; Mary Mbuo; Cissie Namanda; Merlin Willcox (BMC Public Health, 2026)
Introduction Currently, Uganda has the highest per capita alcohol consumption in Africa, and the negative effects of harmful use of alcohol are quite prevalent. Some rural areas face a complex set of underlying factors that may be responsible for this trend, including unemployment and easy access to cheap alcohol. Kigezi sub-region is one of the areas most affected by the harmful use of alcohol. This paper characterizes harmful use of alcohol in form of patterns of use, timing for drinking, types of drinks; and identifies factors associated with it in the sub-region’s tourist area around Lake Bunyonyi. Methods This was a cross-sectional study. A two-stage stratified sample survey was carried out and yielded 339 participants from 34 villages. It had standard questions on alcohol use and included the WHO’s Alcohol Use Disorders Identification Test (AUDIT) score. Harmful alcohol use was assessed using two measures. First, we calculated the proportion of participants with AUDIT scores between 8 and 40, indicating medium- to very high-risk alcohol use (MHA). Second, we used a proxy measure for alcohol use disorder (AUD), defined as the proportion of participants who, in the past 12 months, reported experiencing at least monthly any of the following: loss of control over drinking, alcohol-related failure to meet obligations, or the need for a morning drink after heavy alcohol consumption. The inclusion criteria for participants were adults aged ≥ 18 years, who consented to the study, while the exclusion criterion was withdrawal of consent during the interview process. The factors associated with harmful use of alcohol were determined using multilevel mixed effects generalised linear models that account for the clustering at the village level. Results The prevalence of AUD was 17.7% and of MHA was 28%. The prevalence of MHA was significantly lower among women (APR = 0.47, 0.28–0.76) and higher among those whose relatives or friends condoned alcohol consumption (APR = 1.77, 95% CI: 1.12–2.81), and it increased with improved income level (p < 0.001). Other factors included being more educated, a reduced frequency of engagement with religious activities, and earning a living through skilled trades. Key reasons for stopping alcohol include religious commitment, family background, and observed negative experiences. Most drinkers drink local brew/unrecorded alcohol and prefer to drink at the weekend. Although a few drinkers start drinking before 8am, the number grows to 50% and 60% by 4pm and 5pm respectively. Conclusion Harmful use of alcohol prevalence is higher than what is found in the WHO’s recent nationwide study and other epidemiological studies. The drinking culture leans towards drinking at weekends and daytime drinking and consumption of local brew. The factors associated with harmful use of alcohol include family and friends’ influence, higher income level, and reduced religiosity.
Keywords: Harmful use of alcohol; Uganda; Rural; Prevalence; Two-stage stratified sample; AUDIT score; Mixed effects modelling